HIROSHIMA CITY CONDITION BEFORE AND AFTER BOMBED BY UNITED STATE AS DEPICTED IN JOHNHERSEY'S "HIROSHIMA" : HISTORICALAPPROACH - Henra, Diana; Jusmaya, Ance (SCIENTIA JOURNAL, 2019)
This research is an analysis of Hiroshima City Condition Before and After Bombed by United States as Depicted in John Hersey’s “Hiroshima”: Historical Approach. It is research has two specific objectives of this research, first is to find out the problems faced by the people of Hiroshima before and after the bombing. The second are to find out the facts of the historical facts after bombed. The methodology used in this research is descriptive qualitative method. Data would be gathered from primary source, which is the novel Hiroshima, and secondary sources from various sources, such as history books. The analysis of this study applies the historical approach of Hippolyte Adolph Taine (1872) which explains the race, milieu, and moment. The problem of the Hiroshima community before and after the bombing is proven where many of citizens in Hiroshima lived improperly because the condition of economic matters was paralytic. And the condition be apprehensive is many of citizen in Hiroshima died and were permanently disabled. Then historical facts are also found, namely the surrender of Japan on August 15, 1945 which is announced by the emperor Tenno and the construction of a national monument named the Institute of International Amity. With all these facts, the researchers then concluded that Hiroshima, written by John Hersey indeed contained facts about the fear and anxiety of the Hiroshima community before and after the bombings carried out by United States soldiers.